Go for the goal : a champion's guide to winning in soccer and life - Hamm, Mia, 1972- (Quill, 2000)
Olympic and World Cup soccer champion Mia Hamm discusses her life, tracing her path to success on the field, and offers advice and tips to other girls who would like to follow in her footsteps.